RANCANG BANGUN PENDETEKSI GETARAN GEMPA BERBASIS MIKROKONTROLER IOT ARDUINO - Rustam Effendi; Rd Kania; Mahendra Muhammad (LPPM Unbaja, 2021)
Indonesia, especially in Banten Province, has plates or earthquake lines that not many people know about, so that most areas in Banten Province are heavily affected. Lack of knowledge and lack of information in some areas about this disaster makes ordinary people respond to it. By utilizing Arduino NodeMCU and SW-40 technology as detection sensors that can detect vibrations that occur around the sensor it is installed and as a notification to users and residents of the surrounding community if there is vibration around the sensor which has been connected to an internet network and installs the Blynk application on the device. the user's smartphone, as well as sending notifications in the form of sound, vibration, and message notifications that a vibration occurs, the user can monitor the device from anywhere and anytime. So the author raised the issue with the title